PENGEMBANGAN PERMAINAN JEJAK SUSUN ANGKA UNTUK MENINGKATKAN KEMAMPUAN KERJASAMA PADA ANAK KELOMPOK B TK MUSLIMAT NU 12 AL-MUBAROK PAKISAJI MALANG - No’o, Maria Apolonia; Asmah, Ayu; Emanuel, Sarah (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
This research is motivated by the lack of children in the ability to cooperate, because the tendency of learning to focus on worksheets so that children feel bored and not interested in learning. The purpose of this game development research is to determine the feasibility of the game in improving children's cooperative abilities. The subjects of this study were 14 children in group B at TKM NU 12 Al-Mubarok Pakisaji Malang. This study uses the Research & Development method. The results of the validation of material experts are 94.44%, media experts are 87.5%. Individual trial results 86.11%. The results of field trials were limited to 90.47%. The results of the wider field trial are 97.61%. The ability of children's cooperation can be increased by the presence of a number stacking game, the result of the posttest percentage is higher, namely 89.28% and the pretest with a percentage of 77.38%. From the analysis and discussion of the number stacking game, it can be concluded that the number stacking game is feasible to use in improving children's cooperative abilities. Suggestions are expected to be more innovative in creating learning media that are useful for early childhood.